THE INFLUENCE OF VILLAGE HEAD LEADERSHIP ON COMMUNITY SATISFACTION IN MEKAR JAYA VILLAGE, SEPATAN DISTRICT, TANGERANG REGENCY - Gojali, Muhammad (JURNAL ASIK, 2025)
This study aims to determine the influence of village head leadership on community satisfaction in Mekar Jaya Village, Sepatan District, Tangerang Regency. The background of this study is the importance of leadership in village governance, which is oriented towards public services and community satisfaction. This study used a quantitative approach with a survey method. The sample consisted of 100 respondents selected using a purposive sampling technique, namely residents who had interacted directly with the village head regarding village services or development. The research instrument was a closed-ended questionnaire with two main variables: village head leadership (X) and community satisfaction (Y), each measured through 10 items on a 5-point Likert scale. Validity, reliability, and classical assumption tests were conducted before simple linear regression analysis. The results showed a positive and significant relationship between village head leadership and community satisfaction. The correlation coefficient (r) of 0.701 indicates a strong relationship, while the coefficient of determination (R²) of 0.491 indicates that 49.1% of the variation in community satisfaction can be explained by the village head leadership variable. The t-test results show a calculated t-value of 10.605, which is greater than the t-table value of 1.985. Therefore, H₀ is rejected and H₁ is accepted. Thus, it can be concluded that village head leadership has a significant effect on community satisfaction. The implications of this study indicate that improving leadership qualities, such as openness, fairness, and good communication, are crucial for boosting community satisfaction with public services at the village level